Improving Students’ Reading Comprehension in Report Text Using Herringbone Technique at Ninth Grade Panca Setya 1 Junior High School - Ferdinanda Itu Meo; Ilinawati; Sijono; Otniel Selvindinata (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
This research was motivated by the need to improve reading skills and student performance in reading. Based on preliminary observations, the researcher found the lack of students’ performance and the lack of students' reading comprehension. This research aimed to describe student performance and the improvement of students' reading comprehension skills in report text learning through the implementation of herringbone technique in class IX at Panca Setya 1 Junior High School Sintang. The researcher was used Classroom Action Research which was based on Hopkins design in Keemis, and Mc Taggart, combining both qualitative and quantitative approaches. Qualitative data collection techniques was carried out through observation, interviews, field notes and documentation, while for quantitative data techniques the author used tests to obtain student scores. Qualitative data was analyzed through data reduction, data display, conclusion drawing and verification. While quantitative data were be analyzed using descriptive statistics. The results showed that there was an increase in lack of students’ performance in learning activities and lack of students’ reading comprehension. Student performance in learning activities increased, from 54% in cycle I to 84% in cycle II. In cycle I, the average score of students' reading comprehension was 52, and in cycle II, it was 81.84. It can be concluded that the Herringbone Technique improved students' performance in learning activities and reading comprehension, especially for ninth grade students of Panca Setya 1 Junior High School. The researcher was hoped that the herringbone technique could continue to be used as an effective learning method to improve students' reading skill and participation in class, specifically in English language education.